What about the politics of deconstruction? - Božić Blanuša, Zrinka (Array, 2014)
The essay has two focuses: Europe and community. In his study Europe or the Infinite Task Rodolphe Gasché claims that a vigorous analysis of the concept of Europe may contribute to a better understanding of Europe´s present political crisis. On the other hand, the work of Maurice Blanchot, Giorgio Agamben and especially Jean-Luc Nancy and Roberto Esposito, encourages us to think about community beyond the framework of identity politics. Which questions does this raise in respect to Gasché’s “deconstructive” project? What do these projects, Nancy’s and Esposito’s on one side and Gasché’s on the other, have in common?